Comparison of Clinical Outcomes of Single and Double Soft Anchor Fixation in Arthroscopic Treatment of Anterior Bankart Lesions - Fatih İlker Can; Emre Gültaç; Burak Şener; Rodi Ertoğrul (Muğla Sıtkı Koçman Üniversitesi Tıp Dergisi, 2026)
The aim of this study was to compare the clinical, functional, and stability outcomes of arthroscopic Bankart repair performed using either a single or double soft anchor in patients with limited anterior Bankart lesions between the 1 and 5 o’clock positions. Our retrospective cohort included patients underwent arthroscopic Bankart repair for anterior shoulder instability between January 2018 and December 2023. Glenoid defects or other associated shoulder pathologies were excluded, and all patients had a minimum two years follow-up. The patients were divided into two groups: single soft anchor (n=36) and double soft anchor (n=26). Demographic data, recurrent subluxation/ dislocation, necessity of revision surgery, pain scala, functional outcomes, patient satisfaction rates, and return to sports rates were assessed at the second postoperative year. The mean age was 29.5 ± 7.7 years in the single soft anchor group and 28.0 ± 5.9 years in the double soft anchor group. Recurrent dislocation was observed in three patients in the single soft anchor group, whereas no recurrent dislocation occurred in the double soft anchor group, showing no statistically significant difference between the groups. Pain and functional outcomes were similar between groups at year two, and no statistically significant differences were observed regarding patient satisfaction or return to sports. In patients with limited anterior Bankart lesions, arthroscopic repair using a single soft anchor provides clinical, functional, and stability outcomes comparable to those achieved with double soft anchor fixation.